Peran Public Relation dalam Meningkatkan Citra Universitas Medan Area - Parapat, Rika Wahyuni; Zebua, Ajniver Hamnur; Nurhanifah, Nurhanifah; Sambas, Nayla Aidilla; Irzwansyah, Muhammad Dhio; Hasibuan, Fitrah Al Khairi (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is to examine how the role of public relations in improving the image of the University of Medan Area. In this study, the authors used field research (field research) which is qualitative in nature. This study uses the theory of the four steps of public relations (Research, Planning, Implementation, Evaluation) perspective. This research uses the case study method involving informants from Higher Education Lecturers at UMA and observing the process and results of publications. The results of this study indicate that the strategy carried out by Public Relations in improving the image of the campus is by means of; Improving the quality of learning (lectures and practicum) and the quality of graduation and Improving the quality of the academic atmosphere. Keywords: Role, Public Relations, Citra, University of Medan Area.